Feasibility of Bioimpedance Analysis to Assess the Outcome of Complex Decongestive Therapy in Cancer Treatment-Related Lymphedema - Cho, Kye Hee; Han, Eun Young; Lee, Seung Ah; Park, Hyun; Lee, Chan; IM, Sang Hee (Frontiers in Oncology, 2020)
Background: Cancer treatment-related lymphedema (CTRL) affects patients physically, psychologically and emotionally, and remains a significant quality of life issue among patients with cancer. Reliable methods to measure changes in lymphedema are required for early detection, acute intensive treatment, and long-term management. Here, we evaluated the use of bioimpedance analysis (BIA) as a tool to measure lymphedema before and after treatment. Patients and Methods: Patients with CTRL who were admitted to a secondary university hospital between October 2017 and July 2018 for complex decongestive therapy (CDT) were eligible for this prospective cohort study. Circumferential measure (CM) and BIA were used to evaluate lymphedema at admission (initial) and before discharge (follow-up, FU). Volume was calculated from the CM using the truncated cone formula. The inter-limb ratios (ILRs) of the circumference, volume, and impedance were also calculated as the unaffected limb to affected limb. Each parameter before and after treatment and correlations between parameters also were analyzed. Results: A total of 29 patients (12 upper- and 17 lower-extremity CTRL) completed were included in this analysis. Absolute value and the ILRs of circumference, volume or impedance, and extracellular water/total body water (ECW/TBW) were significantly improved at FU (p<0.01, p<0.05). The initial and FU absolute values, ILRs, ECW/TBW correlated significantly with each other (p<0.01, p<0.05). The cutoff values of ECW/TBW for moderate and severe degree of CTRL were 0.3855 and 0.3955, respectively. The changes of ILRs between initial and FU assessments were significantly different among three groups according to lymphedema severity (p<0.01, p<0.05). Conclusions: BIA data correlates significantly with clinical measurement, and therefore can be a practical tool in monitoring outcome measure after lymphedema treatment. In addition, BIA is more sensitive to subtle changes in lymphedema, and therefore can be useful for the long-term maintenance of lymphedema.